Genetic and migratory evidence for sympatric spawning of tropical Pacific eels from Vanuatu - Schabetsberger, Robert A.; Økland, Finn; Kalfatak, Donna; Sichrowsky, Ursula; Tambets, Meelis; Aarestrup, Kim; Gubili, Chrysoula; Sarginson, Jane; Boufana, Belgees S.; Jehle, Robert; Dall'Olmo, Giorgio; Miller, Michael J.; et al. (Marine Ecology Progress Series, 2015)
The spawning areas of tropical anguillid eels in the South Pacific are poorly known, and more information about their life histories is needed to facilitate conservation. We genetically characterized 83 out of 84 eels caught on Gaua Island (Vanuatu) and tagged 8 eels with pop-up satellite transmitters. Based on morphological evidence, 32 eels were identified as Anguilla marmorata, 45 as A. megastoma and 7 as A. obscura. Thirteen of these eels possessed a mitochondrial DNA sequence (control region, 527 bp) or nuclear haplotype (GTH2b, 268 bp) conflicting with their species designation. These individuals also had multi-locus genotypes (6 microsatellite loci) intermediate between the species, and 9 of these eels further possessed heterozygote genotypes at species-diagnostic nuclear single nucleotide polymorphisms (SNPs). We classified these individuals as possibly admixed between A. marmorata and A. megastoma. One A. marmorata and one A. megastoma migrated 634 and 874 km, respectively, towards the border between the South Equatorial Current and the South Equatorial Counter Current. Both species descended from around 200 m depth at night to 750 m during the day. Lunar cycle affected the upper limit of migration depths of both species. The tags remained attached for 3 and 5 mo and surfaced <300 km from the pop-up location of a previously tagged A. marmorata. A salinity maximum at the pop-up locations corresponding to the upper nighttime eel migration depths may serve as a seamark of the spawning area. The similar pop-up locations of both species and the evidence for admixture suggest that these tropical eels share a sympatric spawning area.
Keywords: Eel; Genotype; Lunar Cycle; Migration; Dna, Mitochondrial; Salinity; Satellite; Sympatry; Telemetry; Vertical Migration; Pacific Ocean; Pacific Ocean (south); Pacific Ocean (tropical); South Equatorial Current; Vanuatu; Anguilla Marmorata; Anguilla Megastoma; Anguilla Obscura; Anguillidae